2022
DOI: 10.3390/ijms232213897
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Immobilised Jagged-1 Enhances Matrisome Proteins Associated with Osteogenic Differentiation of Human Dental Pulp Stem Cells: A Proteomic Study

Abstract: The indirect immobilisation of Jagged-1 (Jagged-1) promoted osteogenic differentiation of human dental pulp cells (hDPs). Furthermore, the analysis of the Reactome pathway of RNA sequencing data indicates the upregulated genes involved with the extracellular matrix (ECM). Hence, our objective was to investigate the effects of Jagged-1 on proteomic profiles of human dental pulp stem cells (hDPSC). hDPSCs were cultured on the surface coated with human IgG Fc fragment (hFc) and the surface coated with rhJagged1/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Indirect affinity immobilization of JAG1 is a common method for JAG1 delivery. For example, protein G has been used by many studies for indirect immobilization and they have demonstrated the functionality of JAG1 in activating the canonical NOTCH gene expression pathway ( Osathanon et al, 2013 ; Manokawinchoke et al, 2017 ; Nowwarote et al, 2018 ; Chansaenroj et al, 2022 ). A 2009 study used self-assembled monolayers for indirect affinity immobilization and it also established the ability of SAMs to allow JAG1-induced NOTCH signaling activation ( Goncalves et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect affinity immobilization of JAG1 is a common method for JAG1 delivery. For example, protein G has been used by many studies for indirect immobilization and they have demonstrated the functionality of JAG1 in activating the canonical NOTCH gene expression pathway ( Osathanon et al, 2013 ; Manokawinchoke et al, 2017 ; Nowwarote et al, 2018 ; Chansaenroj et al, 2022 ). A 2009 study used self-assembled monolayers for indirect affinity immobilization and it also established the ability of SAMs to allow JAG1-induced NOTCH signaling activation ( Goncalves et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this was the first study to demonstrate that JAG1 delivery transiently activates the NOTCH signaling pathway. Chansaenroj et al (2022) was the first study to perform a proteomic study on hDPSCs that were cultured with indirectly immobilized JAG1. Upon extracting the protein component of cells, it was found that JAG1 stimulated the expression of proteins associated with osteogenic differentiation and matrisome proteins played a role in osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation